Assessing the impacts of a utility-scale photovoltaic solar energy facility on birds in the Northern Cape, South Africa. (April 2019) - Visser, Elke; Perold, Vonica; Ralston-Paton, Samantha; Cardenal, Alvaro C.; Ryan, Peter G.
Abstract: Solar energy is a promising alternative to reduce South Africa's dependency on electricity generation from fossil fuels, since the country has one of the world's most favourable solar energy regimes. Utility-scale solar energy developments can impact bird communities through habitat loss and collision mortality, but there are few studies of the impacts of utility-scale photovoltaic (PV) facilities on birds. This study reports how one of South Africa's largest PV facilities (96 MW, 180 ha) has altered bird communities and assesses the risk of avian collision mortality. Bird species richness and density within the PV facility (38 species, 1.80 ± 0.50 birds·ha −1 ) tended to be lower than the boundary zone (50 species, 2.63 ± 0.86 birds·ha −1 ) and adjacent untransformed land (47 species, 2.57 ± 0.86 birds·ha −1 ). Only eight fatalities were detected during 3 months of surveys of the solar field for bird carcasses and other signs of collisions. The extrapolated mortality for the facility was 435 (95% CI 133–805) birds per year (4.5 bird fatalities·MW −1 ·yr −1 ; 95% CI, 1.5–8.5). No threatened species were impacted by the PV facility, but further data are required to better understand the risk of PV solar energy developments on birds. Highlights: Bird species richness and density was lower at the photovoltaic facility than in the surrounding untransformed landscape. Species composition changed between facility and landscape, reflecting the loss of shrub/woodland species. No definitive evidence of bird collision mortality due to solar panels was found. Carcass persistence rates and searcher efficiency influences bird mortality surveys.